Use of Sociable Networking sites as a Teaching tool in Online Classrooms: Enhancing Blended Learning with Social Media and Online Collaboration (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Blended learning has become an efficient teaching method, and it is being adopted byprestigious institutions of higher education all around the world. Blended learning combines face-to-faceinstruction with online resources for a more comprehensive education. Increases in the proportion ofyoung adults enrolled in Haryana‘s universities can be noticed dating back at least a decade. Theybecome extremely proficient in the use of the Internet, social media, and mobile devices. These days,including social media into blended learning is a must. The paper uses a well-known approach, VirtualLearning Environment (VLE), to improve upon e-learning generally. We use the Virtual LearningEnvironment (VLE) dashboard by integrating the Web-based Synchronized Multimedia Lecture (WSML)framework, which allows for the provision of an authoring tool to record the temporal and spatialrelationships among the media involved and facilitate synchronise presentation across media access.This architecture is useful because it facilitates online classroom-style collaboration in real time betweenstudents and instructor(s). Incorporating features of web 2.0 and social media, a VLE allows users tohold meetings through video chat in real time and share and discuss media files with ease. The article'sintended result is a social-media-based learning system that can be used in universities to spice up themonotony of conventional blended-learning settings.